The Relation of Various Durations of Type II Diabetes Mellitus and Endothelial Dysfunction - Alhameed, Mohammed Ali; Jaccob, Ausama Ayob; Alidrisi, Haider A. (Tikrit Journal of Pharmaceutical Sciences, 2024)
Background: Patients with long-term diabetes have a higher prevalence of endothelial dysfunction. Hypercholesterolemia strongly associates this impairment with atherosclerosis, while the duration of diabetes may relate to early macrovascular and microvascular injury. Objectives: The present study assessed the possible relation between various durations of type II diabetes and endothelial dysfunction. Methods: A case-control study of 182 participants included 20 healthy subjects, 30 newly diagnosed diabetes patients, and 132 with varying diabetes durations of type II diabetes. Those patients were divided according to their duration: 50 patients were (1-5 years), 32 patients were (5-10 years), and 50 patients were (more than ten years) in addition to the newly diagnosed group and the healthy control group. Lipid profile, glycemic parameters, and endothelium biomarkers: oxidized nitric oxide (NO), endoglin, intercellular adhesion molecule (ICAM-1), and glutathione were measured. Data was collected from November 20, 2022, to March 31, 2023. Results: Body mass index was significantly elevated in diabetic groups compared to the normal control group. All diabetic groups had highly significant differences in lipid profile and glycemic control parameters compared to the control group. Patients with more than ten years of diabetes had significantly higher (NO) levels than other groups, while the ICAM-1 level in these patients was significantly higher than all other groups. Conclusions: Various duration of type II diabetes was related to endothelial dysfunction that was strongly linked with factors like body mass index, systolic hypertension, hyperlipidemia, and poor control of glycemic index.